Refugia and rupture : critical realism and activist organizing in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Politics and International Relations at Massey University, Manawatū campus, Palmerston North, New Zealand - Thornton, Felix (Massey University, 2026)
This thesis examines the contemporary condition of New Zealand’s extra-parliamentary left (EPL) within the metahistorical context of the Anthropocene, the Capitalocene and the Chthulucene (explored here as the Anthro-Capitalo-Chthulucene). Responding to the question: ‘What is the current social reality such that a left-wing political organisation seeking progressive transformation becomes caught in the impasses of burnout, bureaucracy, and domination?’, the study situates local activist practice within a wider era of intersecting ecological, social, and political crises. Using Critical Realism as a meta-theoretical framework, the research connects empirical organizational breakdown to deeper structural and historical mechanisms shaping contemporary activism. The thesis presents a qualitative textual analysis of reflection documents produced by members of a New Zealand EPL organisation – under the pseudonym MLM NZ – shortly before a mass exodus in 2024. Drawing on Participatory Action Research, Political Activist Ethnography, and Qualitative Data Analysis, the study foregrounds activist voices while maintaining analytical reflexivity. In this research, three central themes emerged: burnout and overcommitment, bureaucratic centralisation, and gendered power dynamics. By placing these findings within both national EPL scholarship and the broader meta-crisis of the Anthro-Capitalo-Chthulucene, the thesis argues that activist organisations are not only responding to crisis but are themselves shaped by it. The concept of refugia is proposed as a framework for resilience, survival, and sustainable political organising in an era where crisis increasingly defines the social terrain. In doing so, this thesis contributes to political scholarship on New Zealand’s extra-parliamentary left movements by demonstrating how organisational fragility can be understood not merely as a failure of strategy, leadership, or ideology, but also as a political outcome shaped by historically produced conditions of crisis, acceleration, and constraint. It advances the argument that the pressures experienced within Aotearoa's EPL organisations mirror broader dynamics of extraction, domination, and exhaustion characteristic of the Anthro-Capitalo Chthulucene. By situating activist breakdown alongside activist possibility, this research reframes contemporary extra-parliamentary politics as a contested terrain in which, reflective engagement with the cycle of formation, deformation and reformation - compositing, in Donna Haraway’s terms - becomes a politically meaningful practice for groups in the extra-parliamentary left.
Keywords: 440809 New Zealand government and politics